Post Operative Outcomes of Single Versus Two Miniplates for Management of Condylar Fractures - Geeta Devi, Usman Manzoor, Muhammad Hamza Hashim, Suneel Kumar Punjabi, Khursheed Ahmed, Bharti, Salman Shams, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To compare the outcomes in patients with single versus two miniplates for condylar fracture. Study Design: Cross-Sectional Study Place and Duration of Study: The study took place in Department of Oral & Maxillofacial Surgery, Institute of Dentistry LUMHS, Jamshoro. The duration of study was 6 months after the approval of the synopsis. Methodology: 40 people in all were included in the trial. A single miniplate was used for Group A's treatment, whereas two miniplates were used for Group B's treatment. Clinical assessment, orthopantomogram (OPG), a P.A. image of the face, and, if necessary, a 3D CT scan will be used to make the diagnosis of condylar fracture.The data was analysed by SPSS version 21 Results: Results of this investigation indicated that the preoperative evaluation of the variables including malocclusion, mouth opening, protrusive movement, and lateral movement revealed greater values, but much less means were found in postoperative examination. ANOVA is done one method to compare the means between preoperative and postoperative malocclusion. The statistical comparison is significant at less than 5%. The examination of platform fracture or bending occurs after the operation, which demonstrates that 92.5% of the population without platform fracture, while 7.5% exhibit platform fracture after surgery. Conclusion: In conclusion, it is indicated that two miniplates with less complicated fixing are superior to a single miniplate. Keywords: condylar fracture, single miniplates, double miniplate, treatment of condylar fracture, post-operative outcomes of condylar fracture.